Novel protein biomarkers associated with coronary artery disease in statin-treated patients with familial hypercholesterolemia - Bos, S.; Phillips, M.; Watts, G.; Verhoeven, A.; Sijbrands, E.; Ward, Natalie (Elsevier Inc., 2017)
© 2017 National Lipid Association Background Familial hypercholesterolemia (FH) is the most common and serious monogenic disorder of lipid metabolism. The incidence of coronary artery disease (CAD) varies among both treated and untreated FH patients. Objective The aim of the study was to utilize proteomics to identify novel protein biomarkers that differentiate genetically confirmed heterozygous patients with FH at high CAD risk from those at low CAD risk. Methods Sixty genetically confirmed FH patients were recruited and stratified into (1) asymptomatic FH with low atherosclerotic burden (FH, n = 20); (2) asymptomatic FH with high atherosclerotic burden (FH + Ca, n = 20); and (3) FH with previously confirmed symptomatic CAD (FH + CAD, n = 20). Results Six new potential proteins were identified; leucine-rich alpha-2-glycoprotein (LRG1), inter-alpha-trypsin inhibitor heavy chain H3, complement C4-B (C4B), complement C1q subcomponent subunit B (C1QB), monocyte differentiation antigen (CD14), and histidine-rich glycoprotein (HRG). There were significant associations between gender and C4B (Z = 2.31, P = .021), C1QB (Z = 2.49, P = .013), CD14 (Z = 2.17, P = .03), and HRG (Z = 2.14, P = .033). There were significant associations between smoking and LRG1 (? 2 2  = 6.59, P = .037), CB4 (? 2 2  = 7.85, P = .02), and HRG (? 2 2  = 6.11, P = .047). All the peptides were significantly associated with advanced CAD stages, independently of age and smoking. However, the absence of the proteins was the strongest marker. The most accurate association with CAD was HRG (area under the receiver operating characteristic curve = 0.922), whereas LRG1, C4B, and C1QB were also associated with CAD (area under the receiver operating characteristic curve > 0.9). For either coronary atherosclerosis or CAD, LRG1, C4B, C1QB, and HRG were relatively well associated. Conclusions The present study has identified 6 novel protein biomarkers that are associated with more advanced stages of atherosclerotic disease and subsequent coronary events in patients with heterozygous FH.